Oliver Twist - Dickens, Charles, 1812-1870. (New York : Oxford University Press, 1996)
In nineteenth-century England, a young orphan boy lives in the squalid surroundings of a workhouse until he runs away and is captured by a gang of thieves, and is finally reunited with his long lost family.
Young Adult
Keywords: Criminals -- England -- London -- Fiction; Orphans -- England -- London -- Fiction; Criminals -- Fiction; Orphans -- Fiction; London (England) -- Social life and customs -- 19th century -- Fiction; London (England) -- 1800-1899 (19th century -- Social life and customs -- Fiction